Софійність світу та духовне зростання особистості у культурі Київської Русі: релігійно-символічний аспект - Гудзенко-Александрук, Олена Георгіївна; Hudzenko-Aleksandruk, Olena H. (Інститут релігієзнавства, філія Львівського музею історії релігії, 2011)
У статті розглядається проблема духовної символіки Київської Русі. При дослідженні символіки, яка представлена культурними досягненнями Київської Русі (мистецтво, література), підкреслена важливість символу Людини з точки зору проблеми духовного формування особистості. In the article the issue of spiritual symbolics of Kyiv Rus is examined. Investigating the symbolism which is represented by cultural achievements of Kyiv Rus (art, literature), the importance of symbol of the Man is underlined for spiritual formation of personality.
Sophian perception of the world and the spiritual perfection of personality in the philosophical culture of Kyiv Rus': the religious and symbolic aspect
Keywords: архетип софійності; духовне зростання особистості; духовна символіка; релігійна символіка; archetype of sophian perception; spiritual perfection of personality; spiritual symbolism; religious symbolism